Scooby-Doo! : the essential guide - Dakin, Glenn (New York : DK, 2004)
A guide to the cartoon characters and scenes connected with Scooby-Doo.
"Featuring movie action from Scooby Doo 2 monsters unleashed"--Cover.
Keywords: Cartoons and comics; Motion pictures; Scooby-Doo (Fictitious character)